Safety of metamizole analgesic therapy in patients with dyspepsia syndrome: a case report - Khoirul Anam; Rina Widiyawat; Tita Sugesti; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Adji Prayitno Setiadi; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
The selection of drugs in patients who have experienced dyspepsia syndrome needs to be studied for its use. Non-steroidal anti-inflammatory drugs (NSAIDs) are a class of drugs that are effective in controlling various inflammatory conditions and treating inflammatory symptoms such as pain but are limited in their use in patients with dyspepsia. We report case of patients with metamizole NSAIDs during three days of hospitalization with a diagnosis of dyspepsia. Other side effects such as cardiovascular, neurological disorders and agranulocytosis can also occur with the use of metamizole. There were no side effects that exacerbated dyspepsia symptoms in patients or other side effects during the three days of using metamizol. It can be concluded that short-term metamizole therapy is safe for use in patients with dyspeptic syndrome. Concomitant use with gastric acid blocking agents such as H2 receptor antagonists may also reduce the effects of gastrointestinal disturbances.